Antimicrobial and Antibiofilm Activity of Chitosan Nanoparticles Against Staphylococcus Aureus Strains Isolated from Bovine Mastitis Milk - Gamboa-Arancibia, A (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Bovine mastitis (BM), a prevalent and economically burdensome bacterial infection affecting dairy cattle, poses a significant challenge to the dairy industry. The traditional approach to combating BM, relying heavily on antibiotics, faces growing concerns due to the increasing antibiotic resistance exhibited by pathogens. The objective of this study was to evaluate and determine the antimicrobial and anti-biofilm potential of chitosan nanoparticles (NQo) on S. aureus strains isolated from milk samples obtained from dairy areas in southern Chile from cows diagnosed with BM. Methods: NQo were synthesized using the ionotropic gelation method and thoroughly characterized by transmission electron microscopy (TEM) and dynamic light scattering (DLS). Results: The NQo exhibit a robust positive charge (Z-potential of +55.4 ± 2.5 mV) and an exceptionally small size (20.3 ± 3.2 nm). This unique combination of properties makes NQo particularly well-suited for targeting and interacting with bacterial pathogens. To assess the effectiveness of NQo against BM, we conducted a series of experiments using a Staphylococcus aureus strain isolated from milk samples of cows diagnosed with BM in southern Chile. NQo demonstrated a remarkable ability to inhibit bacterial proliferation and effectively modulate biofilm formation in the S. aureus strains. Furthermore, the performance of NQo in comparison to established antibiotics like ampicillin and gentamicin strongly suggests that these nanoparticles hold immense potential as an attractive alternative for the control, prevention, and/or treatment of BM. Conclusions: NQo exhibit both antimicrobial and antibiofilm activity against a clinically relevant BM pathogen. Further investigations are necessary to develop a hydrogel formulation optimized for effective delivery to the target diseased tissue. © 2025 by the authors.